USING PEER ASSISTED LEARNING STRATEGY ON READING COMPREHENSION OF ANALYTICAL EXPOSITION - Budiyanto, Darmawan (Jurnal Ilmiah Bina Edukasi, 2019)
The objective of this study was to find out whether or not there was any significant difference on reading comprehension of analytical exposition that were taught by using Peer Assisted Learning strategy (PALS) and those who were not, and to find out whether or not it was effective to use PALS on reading comprehension. This study used quasi experimental method. 78 students was taken as sample, consists of 39 students XI IPS 3 as experimental group and XI IPS 4 as control group. Test was used in collecting data as pretest and posttest. To verify the hypothesis, the result of independent sample t-test found that t-obtained (11.077) was higher than t-table (1.9917) with df(=76), and the significance 2-tailed was 0.000. It means that there was any significant difference on reading comprehension that were taught by using PALS and those who were not, and also it was effective to use PALS.